In Gromov's book Partial Differential Relations, a partial differential operator (PDO) is defined as follows. Given a fibration $X\to V$ and a vector bundle $G\to V$ over a manifold $V$, a PDO of order $k$ is a map $D:\Gamma(X)\to \Gamma(G)$, satisfying $D(x)=\Delta\circ j^k_x$ for every $x\in \Gamma(X)$, where $\Delta:X^{(k)}\to G$ is a bundle map. Here $X^{(k)}$ is the $k^{\text{th}}$ jet bundle of sections of $X\to V$ and $j^k_x$ is the $k^{\text{th}}$ jet of $x$.

Now, say $G$ is some tensor bundle on $V$ and $X=TV$. Then for a fixed section $\omega\in\Gamma(G)$, we have an operator, \begin{align*} D_\omega:\Gamma(TV)&\to \Gamma(G)\\ x&\mapsto \mathcal{L}_x(\omega) \end{align*} where $\mathcal{L}_x(\omega)$ is the Lie derivative of the tensor $\omega$ along the vector field $x$.

How do I see that this $D_\omega$ is indeed a partial differential operator of order 1, as defined by Gromov? In particular, I would like to find out the bundle map $\Delta=\Delta_w$ such that $D_\omega(x)=\Delta\circ j^1_x$.

For the case $G=\Lambda^k T^*V$, I can use the Cartan's formula and get, $$D_\omega(x)=\mathcal{L}_x(\omega)=d\iota_x(\omega)+\iota_xd\omega$$ I do know that the exterior derivative map $d$ can be seen as a PDO. But I still can't see how to get to the map $\Delta$. And I'm in complete loss when $G$ is an arbitrary tensor bundle, since in that case the Lie derivative is defined using flows.

Any help regarding this appreciated.


3 Answers 3


There is another way to show something is a linear partial differential operator. One can characterize partial differential operators in a coordinate-free manner using commutators:

Let $E\to M$ and $F\to M$ be two vector bundles over $M$. Consider the set, $\mathcal{L}(\Gamma(E),\Gamma(F))$, of $\mathbf{R}$-linear operators between sections of $E$ and sections of $F$. Now define $\mathbf{PDO}_0(E,F):=\mathrm{hom}(E,F)$; note that this coincides with the local definition of an order $0$ differential operator. The key observation is that by considering a differential operator $D$ of order $k$ and looking at the commutator $[D,f](\sigma):=D(f\sigma)-fD(\sigma)$ that the degree of the differential operator decreases by $1$. In some sense, it cancels out the Leibniz rule.

For example, if $D\in\mathbf{PDO}_0(E,F)$ we have for any $f\in\mathscr{C}^\infty(M)$ and $\sigma\in\Gamma(E)$ that $[D,f](\sigma)=D(f\sigma)-fD(\sigma)=0$.

Now we can equivalently give an inductive definition of order $k$ partial differential operators as $$\mathbf{PDO}_k(E,F):=\{D\in\mathcal{L}(\Gamma(E),\Gamma(F))~:~[D,f]\in\mathbf{PDO}_{k-1}(E,F)~\text{ for all }f\in\mathscr{C}^\infty(M)\}.$$ It shouldn't be too difficult to show the equivalence of this definition with that given by factorization through the $k^\mathrm{th}$ Jet space of $E$. The advantage of this definition is that it makes it very easy to show that a operator is a order $k$ partial differential operator $-$ we simply have to show that $k+1$ successive commutators of the operator is zero.

Now given this characterization of partial differential operators, we see immediately see that the Lie derivative is a differential operator of order $1$: Let $E=F=T^{s}_{r}M$ denote the $r$-times contravariant and $s$-times covariant tensor product. Fix a vector field $X\in\Gamma(T^0_1M)$, and consider any smooth functions $f,g\in\mathscr{C}^\infty(M)$ and a tensor field $T\in\Gamma(E).$ We have by using the Leibniz rule of the Lie derivative, \begin{align*} [[\mathscr{L}_X,f],g](T)& =[\mathscr{L}_X,f](gT)-g[\mathscr{L}_X,f](T)\\& =\mathscr{L}_X(fgT)-f\mathscr{L}_X(gT)-g\mathscr{L}_X(fT)+fg\mathscr{L}_X(T)\\ & = (\mathscr{L}_X(fg))T+(fg)\mathscr{L}_X(T)-f\mathscr{L}_X(g)T-(fg)\mathscr{L}_X(T)\\ &\qquad -g\mathscr{L}_X(f)T-(fg)\mathscr{L}_X(T)+(fg)\mathscr{L}_X(T)\\ & = \mathscr{L}_X(fg)T-f\mathscr{L}_X(g)T-g\mathscr{L}_X(f)T\\ & = 0. \end{align*} EDIT: I made the mistake of considering the differential operator $\mathscr{L}_X:\Gamma(E)\to\Gamma(E)$ for a fixed vector field $X\in\Gamma(TM)$, instead of what was asked in the question: Fix a tensor field $\omega\in T^s_rM$ for some $r,s\in\mathbf{N}$, and consider the operator $D_\omega:\Gamma(TM)\to\Gamma(T^s_rM)$ given by $X\mapsto\mathscr{L}_X\omega$. Note that in the case $\omega\in\Omega_k(M)$ is a differential $k$-form, it is very straightforward to see that $D_\omega\in\mathbf{PDO}_1(TM,\bigwedge^kTM^*)$ $-$ recall the identity $$\mathscr{L}_{fX}\omega=f\mathscr{L}_X\omega + df\wedge\iota_X\omega,\qquad f\in\mathscr{C}^\infty(M).$$ Now fix $X\in\Gamma(TM)$ and $f,g\in\mathscr{C}^\infty(M).$ A direct computation shows that \begin{align*} [[D_\omega,f],g](X) & = [D_\omega,f](gX) - g[D_\omega,f](X) \\ & = D_\omega(fg X) - fD_\omega(gX) - gD_\omega(fX) + fgD_\omega(X) \\ & = \mathscr{L}_{fgX}\omega - f\mathscr{L}_{gX}\omega - g\mathscr{L}_{fX}\omega + fg\mathscr{L}_{X}\omega \\ & = fg\mathscr{L}_{X}\omega +d(fg)\wedge\iota_X\omega - fg\mathscr{L}_{X}\omega - fdg\wedge\iota_X\omega \\ & \qquad -fg\mathscr{L}_{X}\omega - gdf\wedge\iota_X\omega +fg\mathscr{L}_{X}\omega \\ & = d(fg)\wedge\iota_X\omega - fdg\wedge\iota_X\omega - gdf\wedge\iota_X\omega \\ & = 0. \end{align*} So we have demonstrated that $D_\omega\in\mathbf{PDO}_1(TM,\bigwedge^kTM^*).$

I found it to be a little bit messier to consider an arbitrary $(r,s)$-type tensor. I don't know if there are any nifty identities for $\mathscr{L}_{fX}T$ for smooth functions $f$, vector fields $X$, and tensor fields $T$. Nevertheless there isn't really anything deep going on in the following computations. Recall that we can consider $(r,s)$-type tensors as multilinear maps from $(\Omega_1(M))^r\times(\Gamma(TM))^s\to\mathbf{R}$. Under this natural isomorphism it isn't hard to show \begin{align*} (\mathscr{L}_XT)(\alpha^1,\dots,\alpha^r,Y_1,\dots,Y_s)&=X(T(\alpha^1,\dots,\alpha^r,Y_1,\dots,Y_s))-\sum_{j=1}^{r}T(\alpha^1,\dots,\mathscr{L}_X\alpha^j,\dots,\alpha^r,Y_1,\dots,Y_s) \\&\quad - \sum_{k=1}^{s}T(\alpha^1,\dots,\alpha^r,Y_1,\dots,\mathscr{L}_XY_k,\dots,Y_s), \end{align*} where $X\in\Gamma(TM)$, $T\in\Gamma(T^s_rM)$, $\alpha_j\in\Omega_1(M)$, and $Y_k\in\Gamma(TM).$ For simplicity, I will write $\vec{\alpha}=(\alpha^1,\dots,\alpha^r)$ and $\vec{Y}=(Y_1,\dots,Y_s).$ In particular, we see that for some $f\in\mathscr{C}^\infty(M)$ that \begin{align*} (\mathscr{L}_{fX}T)(\vec{\alpha},\vec{Y}) & = f(\mathscr{L}_XT(\vec{\alpha},\vec{Y})) - \sum_{j=1}^{r}T(\alpha^1,\dots,df\wedge\iota_X\alpha^j,\dots,\alpha^r,\vec{Y}) + \sum_{k=1}^{s}df(Y_k)T(\vec{\alpha},Y_1,\dots,X,\dots,Y_s). \end{align*} Now we compute for arbitrary $f,g\in\mathscr{C}^\infty(M)$, $T\in\Gamma(T^s_rM)$, $\vec{\alpha}\in(\Omega_1(M))^r$, and $\vec{Y}\in(\Gamma(TM))^s$: \begin{align*} & ([[D_T,f],g](T))(\vec{\alpha},\vec{Y}) = D_T(fg X) - fD_T(gX) - gD_T(fX) + fgD_T(X) \\ & = fg(\mathscr{L}_X(T)(\vec{\alpha},\vec{Y})) - \sum_{j=1}^{r}T(\alpha^1,\dots,d(fg)\wedge\iota_X\alpha^j,\dots,\alpha^r,\vec{Y}) + \sum_{k=1}^{s}d(fg)(Y_k)T(\vec{\alpha},Y_1,\dots,X,\dots,Y_s) \\ & \quad - fg(\mathscr{L}_X(T)(\vec{\alpha},\vec{Y})) + f\sum_{j=1}^{r}T(\alpha^1,\dots,dg\wedge\iota_X\alpha^j,\dots,\alpha^r,\vec{Y}) - f\sum_{k=1}^{s}dg(Y_k)T(\vec{\alpha},Y_1,\dots,X,\dots,Y_s) \\ & \quad - fg(\mathscr{L}_X(T)(\vec{\alpha},\vec{Y})) + g\sum_{j=1}^{r}T(\alpha^1,\dots,df\wedge\iota_X\alpha^j,\dots,\alpha^r,\vec{Y}) - g\sum_{k=1}^{s}df(Y_k)T(\vec{\alpha},Y_1,\dots,X,\dots,Y_s) \\ & \quad + fg(\mathscr{L}_X(T)(\vec{\alpha},\vec{Y})) \\ & = 0. \end{align*} To get that it's equal to zero I simply used the multilinearity of all of the mappings involved and that $d(fg)=fdg + gdf$. I tried to make it easier to read by having each line include only one expansion of the terms above In particular, since $\vec{\alpha}$ and $\vec{Y}$ were arbitrary we deduce that $[[D_T,f],g]=0,$ and so $D_T\in\mathbf{PDO}_1(TM,T^s_rM)$ as desired.

In light of all of the above examples, we see that this characterization does indeed make it very straightforward to show that an operator is indeed an order $k$ partial differential operators. Another example: it's easy to use the above to see that the exterior derivative is a PDO of order at most $1.$

  • 2
    $\begingroup$ That's actually a very helpful description. I've yet to work out the details, but one thing. The operator that I'm interested in is $X\mapsto\mathscr{L}_X(\omega)$ for a fixed tensor $\omega$. So, it requires $E=TM$ and $F=T^s_r M$. But I think your argument will still work, with little modification. $\endgroup$
    – ChesterX
    Jun 23, 2017 at 17:22
  • 1
    $\begingroup$ Ahh, my bad. It should still work. It definitely holds for differential forms in light of the following identity: $\mathscr{L}_{fX}\alpha=f\mathscr{L}_X\alpha + df\wedge\iota_X\alpha$. I think we have something similar for the Lie derivative of arbitrary tensor fields. I will update the answer with the more details later tonight. $\endgroup$ Jun 23, 2017 at 18:00
  • 1
    $\begingroup$ @ChesterX I just edited my answer to include to consider the operator $X\mapsto\mathscr{L}_X\omega$ for a fixed tensor field $\omega$. There isn't really anything deep going on, just a few more computations. I hope it helps! $\endgroup$ Jun 23, 2017 at 20:34
  • $\begingroup$ Is there a textbook or other reference you’d recommend for this inductive characterization of partial differential operators (and related material in your answer)? $\endgroup$ Jun 11, 2021 at 1:49

The statement can be proven by induction.

Let $\omega_1$ and $\omega_2$ be tensors which satisfy the property. That is, the operators $X\mapsto\mathcal{L}_X\omega_1$ and $X\mapsto\mathcal{L}_X\omega_2$ are differential operators of order $1$. By the Leibniz rule,$$\mathcal{L}_X(\omega_1\otimes\omega_2)=(\mathcal{L}_X\omega_1)\otimes\omega_2+\omega_1\otimes(\mathcal{L}_X\omega_2),$$and it follows immediately that $X\mapsto\mathcal{L}_X(\omega_1\otimes\omega_2)$ is also a differential operator of order $1$.

You already know the statement is true for $1$-forms. It is also true for vector fields, as $\mathcal{L}_XY=[X,Y]$. Since the tensor algebra is generated by vector fields and $1$-forms, we are done.


Here, $X$ is $\Lambda ^kT^*V$, $G=\Lambda ^kT^*V$, and in local coordinates, one see that $L_X$ is a bundle map, once $X$ is fixed, namely the coordiantes of $L_X \omega$ linearly depend on the one jet of the coordinates of $\omega$. For instance if $\omega= \sum \omega _idx^i$ then$L_X \omega= \sum _{i\not = j} X_j \partial _j \omega _i dx^i\wedge dx ^j$

  • $\begingroup$ Actually the operator that I'm looking into is $D_\omega:X\mapsto \mathcal{L}_X(\omega)$, for a fixed $\omega$. So, $G=\Lambda^k T^*V$ and $X=TV$ $\endgroup$
    – ChesterX
    Jun 23, 2017 at 17:13

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.